Perspective on stroke in Mexico - Góngora Rivera, Juan Fernando (UANL. Facultad de Medicina, 2015)
According to the World Health Organization’s world health report 2004, cerebral-vascular disease --- stroke --- is the third leading cause of premature death in both genders. Its greatest impact is represented as the leading cause of disability in adults and the second leading cause of dementia.